Computing Colour Image Processing Digital Colour Primer - Parkin, Alan (Springer International Publishing, 2018)
This book proposes a new approach to colour in digital images, based on the standard sRGB colour space and Python scripting. It covers creating, storing, processing, displaying, printing, and viewing colour images. The fundamental ideas presented include systematic reduction of colour resolution to manageable sRGB sub-spaces, analysis of any image as a tabular colour scheme, general transformation and specific substitution of colours, and revival of the traditional notion of a neutral balance by adjusting all colours or by adjoining a colour frame. The text includes Python scripts for the processes discussed, downloadable in the e-book. It is of interest to artists, designers, and anyone who works with sRGB colour images. .